IMF Financial Operations 2014. (Books; 2014, 2014)
IMF Financial Operations 2014 provides a broad introduction to how the IMF fulfills its mission through its financial activities. It covers the financial structure and operations of the IMF and also provides background detail of the financial statements for the IMF's activities during the most recent financial year. This publication updates a previous report entitled Financial Organization and Operations of the IMF, first published in 1986 and last issued in 2001 (the sixth edition). That 2001 report reflected the seismic shifts in the global economy and in the IMF's structure and operations that occurred after the fall of the Soviet Union and the various currency and financial crises of the 1990s. This revised and updated report covers more recent developments, including measures taken in response to the global financial crisis of 2007-09 and the institutional reforms aimed at ensuring that the IMF's governance structure evolves in line with developments in the global economy, as well as reforms to the IMF's income model.